Wine tasting based on emotional responses: an expedite approach to distinguish between warm and cool climate dry red wine styles - Coste, Amaury (2020)
In this study, we improved an empirical tasting sheet including emotional responses and common sensory attributes. An Optimized Descriptive Profile (ODP) was run to characterize different red wines according to sensory descriptors used in the improved sheet. A total of 5 wines were evaluated by a Consumer Panel (CP) of 103 subjects (36 females, 67 males) using the improved sheet and a Check-All-That-Apply (CATA) list of 25 emotions. In the ODP, the panel identified the main discriminating sensory attributes as “Complexity”, “Astringency” and “Duration of the wine fragrance”. However, this analysis did not allow for differentiating very distinct dry red wine styles originating from warmer or cooler regions. On the contrary, Principal Component Analysis of emotional attributes demonstrated that these two wine styles could be easily distinguished. In particular, wine with a red-brick color, complex smell and aggressive mouthfeel consistent with those from cooler regions was less liked by the CP than a warm climate gold-awarded wine. Although receiving lower scores considering its color and smell, the former wine was regarded as the most “surprising” in the CATA